The Conductivity Measure for the Anderson Model - Klein, Abel; Müller, Peter (Журнал математичної фізики, аналізу, геометрії, 2008)
We study the ac-conductivity in linear response theory for the Anderson tight-binding model. We define the electrical ac-conductivity and calculate the linear-response current at zero temperature for arbitrary Fermi energy. In particular, the Fermi energy may lie in a spectral region where extended states are believed to exist. Mathematics Subject Classification: 82B44, 47B80, 60H25.